Cyclic behavior and constitutive model of high strength low alloy steel plate. (15th August 2020) - Jia, Chen; Shao, Yongsong; Guo, Lanhui; Liu, Hongbo
Highlights: The LCF failure and ELCF failure of the high strength low alloy steel plate showed different fracture characteristics. The high strength low alloy steel plate represented obvious cyclic softening and good energy dissipation performance. The cyclic stress–strain curve of the high strength low alloy steel plate could be described by the Ramberg-Osgood model. A suitable constitutive model was calibrated to simulate the cyclic behavior of the high strength low alloy steel plate. Abstract: Cyclic loading tests with different protocols were conducted for a high strength low alloy steel. Based on the test results, the low cycle fatigue and extremely low cycle fatigue performance of the high strength steel was discussed and an appropriate constitutive model was established. The experimental results implied that the low and extremely cycle fatigue failure showed different fracture features. For low cycle fatigue, there was a strong negative linear correlation between the fatigue life and the strain amplitude in the log–log scale. However, they did not conform the linear relation when transiting to the low cycle fatigue. The steel represented obvious cyclic softening and good energy dissipation capacity. With the increase of strain amplitude, the softening degree decreased and equivalent damping ratio increased. The cyclic stress–strain curve could be descried by the Ramberg-Osgood model, and the strength coefficient and strain hardening exponent of this steel were larger than those of steel with lower strength. A combined hardening model was calibrated to describe the cyclic plasticity of the steel, and it was verified by the simulation results.